A 3D Finite Element Thermal Model for Clothed Human Body (Journal of Fiber Bioengineering and Informatics, 2013)
A heat and moisture transfer model for the clothed human body is developed based on the 3-D scanningdata of the human body. The whole passive clothed human body system is subdivided into four sub-systems which are the tissue system, the circulatory system, the respiratory system and the clothingsystem. The physical process of the heat and moisture transfer in the each sub-system is described byenergy and mass balance equations. The Finite Element Method (FEM) is used to solve the governingequations for each sub-system. For a multi-layer clothing sub-system, a simple solution scheme is givenby defining the air element. Also, the model is validated by comparing the simulation with experimentalresults from the literature. Finally, the 3-D simulation results are shown. The conclusion shows that themodel has good prediction ability and it can be applied in the clothing design.
Keywords: Heat and Moisture Transfer; Human Body; Clothing; Model; Finite Element Method